Pengaruh Brand Image, Brand Trust dan E-Wom terhadap Keputusan Pembelian Makanan Menggunakan Jasa Shopeefood di Kota Palembang - Vika Diwinta Aulia; Sulastri Sulastri; Ahmad Maulana; Aslamia Rosa (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted aiming to determine the effect of brand image, brand trust and electronic word of mouth on food purchasing decisions using ShopeeFood services in Palembang City. The sample in this study were 108 consumers who were obtained through a sampling technique using quota sampling and purposive sampling. The data collection method uses a questionnaire which is distributed to all consumers and the data is processed using Structural Equation Modeling (SEM). The results showed that brand image and brand trust had a positive effect on purchasing decisions, while electronic word of mouth had no effect on food purchasing decisions using ShopeeFood services in Palembang City. Keywords: Brand Image, Brand Trust, Electronic Word of Mouth, Purchase Decision, ShopeeFood